BAF (mSWI/SNF) complex regulates mediolateral cortical patterning in the developing forebrain - Nguyen, Huong; Sokpor, Godwin; Parichha, Arpan; Pham, Linh; Saikhedkar, Nidhi; Xie, Yuanbin; Ulmke, Pauline Antonie; Rosenbusch, Joachim; Pirouz, Mehdi; Behr, Rüdiger; Stoykova, Anastassia; Brand-Saberi, Beate; et al. (Frontiers in Cell and Developmental Biology, 2022)
Early forebrain patterning entails the correct regional designation of the neuroepithelium, and appropriate specification, generation, and distribution of neural cells during brain development. Specific signaling and transcription factors are known to tightly regulate patterning of the dorsal telencephalon to afford proper structural/functional cortical arealization and morphogenesis. Nevertheless, whether and how changes of the chromatin structure link to the transcriptional program(s) that control cortical patterning remains elusive. Here, we report that the BAF chromatin remodeling complex regulates the spatiotemporal patterning of the mouse dorsal telencephalon. To determine whether and how the BAF complex regulates cortical patterning, we conditionally deleted the BAF complex scaffolding subunits BAF155 and BAF170 in the mouse dorsal telencephalic neuroepithelium. Morphological and cellular changes in the BAF mutant forebrain were examined using immunohistochemistry and in situ hybridization. RNA sequencing, Co-immunoprecipitation, and mass spectrometry were used to investigate the molecular basis of BAF complex involvement in forebrain patterning. We found that conditional ablation of BAF complex in the dorsal telencephalon neuroepithelium caused expansion of the cortical hem and medial cortex beyond their developmental boundaries. Consequently, the hippocampal primordium is not specified, the mediolateral cortical patterning is compromised, and the cortical identity is disturbed in the absence of BAF complex. The BAF complex was found to interact with the cortical hem suppressor LHX2. The BAF complex suppresses cortical hem fate to permit proper forebrain patterning. We provide evidence that BAF complex modulates mediolateral cortical patterning possibly by interacting with the transcription factor LHX2 to drive the LHX2-dependent transcriptional program essential for dorsal telencephalon patterning. Our data suggest a putative mechanistic synergy between BAF chromatin remodeling complex and LHX2 in regulating forebrain patterning and ontogeny.